EVALUASI MUTU PROSES PERKULIAHAN MATA KULIAH AKUNTANSI DI JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI BALI - Wayan Suryathi; Ketut Vini Elfarosa (Soshum: Jurnal Sosial dan Humaniora, 2013)
This research entitled evaluation of lecturing process quality of accountancy subject which aimed to examine two cases in evaluating accountancy subject in the Bussines Administration Departement.To measure whether or not students have different perspective or assessment to the lecturing process quality of accountancy subject in the trade administration program PNB. The student’s assessment results to the lecturing process quality of accountancy subject in trade administration program PNB. The student assessment result is analyzed by determining the percentage of respondents’ answer in which was obtained the research result of 50 samples of student as follows: 39 students (78%) with good category assessment, 6 students (6%) with neural category assessment,16 students (8%) with not good category assessment This measurement results were analyzed by chi-square pattern was obtained the result from 50 samples of students, X2 = 6,830. Its value lower than the value of X2 (its critical value), in which with it degree of freedom (df) = 4 (chi-square) and level of significant 95%, the critical value was obtained = 9,49 or with the level of significant 99% was obtained the critical value = 13,28. Therefore, the calculated value/e of X2 (6,830) lower than the critical value (9,49 or 13,28), thus, it can be concluded that there is no different assessment or perception significantly among the students who got value of A, B, and even C toward the lecturing process quality of accountancy subject in trade administration program of PNB.